Diagnostic and treatment problems with parosteal osteosarcoma - Samardziski, Milan (Radiology and oncology (Ljubljana), 2007)
Background. Parosteal osteosarcoma is a rare low-grade bone tumour. The operation material must undergo a careful patohistological analysis, because the extent of invasion of the medullar cavity and most probably the extent of dedifferentiated areas determines the prognosis and occurrence of local recurrence and metastases. Patients and methods. In this retrospective clinical study, 7 cases of parosteal osteosarcoma of the bone have been analyzed. Six patients were with parosteal osteosarcoma and one with periosteal osteosarcoma. The study was performed at the Clinic for Orthopedic Surgery in Skopje, Macedonia, from 1995 to 2006. This tumour represents 1.5% of all 467 patients with primary bone tumours treated at the Clinic in the 12 year period. The age of 7 patients (3 female and 4 male) ranged from 8 to 39 years (median 27). The history analysis of the patients showed the misinterpreted diagnosis in 57% of the cases, with 71.4 % rate of local recurrence, 28.7% of metastases and 28.7% of mortality. The follow-up varied from 7 months to 9 years (median 37 months). Results. The clinical and histopathological findings of this study (same as those reviewed in the literature) confirmed the occurrence of two biologically different types of parosteal osteosarcoma: the predominant type is originally ĆbenignĆ but has a definite malignant potential, causing metastases after the long symptom- free interval. The other type is highly malignant from the beginning. Conclusions. The compartmental, radical Ćen blocĆ resection, followed by the regular reviewof the patients, is recommended for the low malignant type, however, theradical surgery, followed by chemotherapy, is recommended for the highly malignant tumours.
Keywords: bolezni kosti; Diagnosis; diagnostika; okostje; Osteosarcoma; Osteosarkom; Periosteum; Pokostnica; rak (medicina); Therapy; zdravljenje